A distributed security tomography framework to assess the exposure of ICT infrastructures to network threats. (June 2021) - Brignoli, M.A.; Caforio, A.P.; Caturano, F.; D'Arienzo, M.; Latini, M.; Matta, W.; Romano, S.P.; Ruggiero, B.
Abstract: The scope of cyber security becomes wider and wider with time and cyber threats rapidly change. This strongly impacts the performance of companies whose success heavily depends on the health of the underlying network infrastructure. The ability to have a clear understanding of the security exposure of a network in its entirety hence becomes part of the mission of such companies. In this work we present the design and implementation of a distributed measurement solution to assess the cyber security exposure of an ICT Infrastructure. We provide means to define cyber security indicators through an automated and repeatable measurement process. We prove the efficiency of the presented methodology by testing it on real-world infrastructure facilities, discussing the results obtained in two different scenarios: a comparison of networks with different characteristics and a real-time monitoring of the defined metrics.